Switching escape strategies in the parasitic ant cricket Myrmecophilus tetramorii - Ryoya Tanaka; Yuki Mitaka; Daigo Takemoto; Mitsuhiko P. Sato; Azusa Kamikouchi; Yoshinori Suzuki (Communications Biology)
Abstract Social parasites employ diverse strategies to deceive and infiltrate their hosts in order to benefit from stable resources. Although escape behaviours are considered an important part of these multipronged strategies, little is known about the repertoire of potential escape behaviours and how they facilitate integration into the host colony. Here, we investigated the escape strategies of the parasitic ant cricket Myrmecophilus tetramorii Ichikawa (Orthoptera: Myrmecophilidae) toward its host and non-host ant workers. We identified two escape strategies with distinct trajectory characteristics by clustering analysis; distancing (defined by high-speed straight movement away from ants for emergency avoidance) and dodging (circular escape movement to get behind ants under low-threat conditions). Interestingly, dodging is dominantly elicited over distancing for host species. Furthermore, our simulations proposed that dodging contributes to efficient foraging while avoiding ants. These results demonstrate that switching to a host-adapted escape strategy facilitates integration of this parasitic cricket into ant nests.